A PLL based mechanical faults detection in PMSM at variable speed. Issue 24 (2018) - Allouche, Abdallah; Etien, Erik; Doget, Thierry; Rambault, Laurent; Sakout, Anas; Cauet, Sébastien; Martin, Pascal
Abstract: In electrical motors, angular speed contains crucial information about mechanical faults but their detection is difficult when the motor is running at variable speed. In this paper, a technique based on a Phase-Locked Loop (PLL) allows on the one hand to estimate the angular velocity of the motor and on the other hand to synchronize the signals with respect to the angular position in order to simplify the analysis. The proposed method is validated with simulations and real tests performed in an original experimental setup.